Development of a high power fibre laser for laser based electron beam diagnostics - Corner, L; Nevay, L; Delerue, N; Howell, D; Newman, M; Walczak, R; Blair, G; Boogert, S (European Physical Society Accelerator Group (EPS-AG), 2008)
We present the latest results on the development of a high power fibre laser system for use in a linear collider laser-wire experiment. The laser consists of a solid state oscillator which can be synchronised to an external frequency reference, and two amplification stages in double clad doped fibre, giving 1μJ pulses in a burst mode suitable for a linear collider laser-wire system. This output is amplified in large mode area photonic crystal fibre to generate the high pulse energy necessary for Compton scattering without any deleterious nonlinear effects, whilst maintaining the high spatial mode quality and beam pointing stability of a fibre laser. These properties are essential for producing the sub-micron spot sizes required for the measurement of small particle beam sizes.